The development of power electronics training kits for electrical engineering students: A validity test analysis - Dewi, Citra; Yanto, Doni Tri Putra; Hastuti, Hastuti (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This study discusses one of the stages of the research in the development of the Power Electronics Training Kits in the learning process of the Power Electronics Practicum for Electrical Engineering students, namely the validity test analysis. The validity of the Power Electronics Training Kits is divided into three aspects, namely design, media/laboratory equipment, and materials aspects. Each of these aspects was validated each by two validators who had expertise in these aspects. The instrument used in testing this validity was a validated questionnaire that had gone through the previous instrument validation process. The analysis was carried out using Aikens V Analysis. Validity analysis results are interpreted with the product development validity interpretation table by Aiken's to obtain the validity category. The results showed the Training Kits is valid in all aspects both aspects of design, media/laboratory equipment, and materials. The design aspect gained a value of V = 0.89 with a valid category, the media/laboratory equipment aspect gained a value of V = 0.88 which means valid, and the material aspect gained a value of V = 0.94 with a valid category. Thus, it can be concluded that the Power Electronics Training Kits developed for the learning process of the Power Electronics Practicum for Electrical Engineering students is valid in the aspects of design, media/laboratory equipment, and materials.